Analysis of the Development of Image Media Use on Science Learning Outcomes in Primary Schools In the period 2018-2023 - Meliyana Meliyana; Rohmani Rohmani (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: Technological developments regarding image media have increased quite significantly in the last six years, where the impact of the use of visual media on science learning outcomes at both middle school and high school levels, especially elementary school, is very popular, and there has been an increase in research on both theses and SINTA articles. The goal of this study is to find out how much the usage of visual media affects science learning outcomes. Topics covered in elementary school. Method: A Systematic Literature Review (SLR) methodology is used in this investigation. This methodology makes the examination and synthesis of recent research findings in primary school education possible. Using the PRISMA methodology, the study carried out a systematic literature review, covering steps like identification, screening, eligibility assessment, and inclusion criteria. The literature sources covering 2018 to 2023 came from the Google Scholar or Google Scholar database. The conclusions of this research come from database searches carried out using the terms Image Media, Science Learning Results, and Primary School. Results: Once the literature search was completed, the analysis yielded ten articles that met the requirements for inclusion in the detailed analysis. This is selected and included. Novelty: To ensure students achieve the highest academic success, the application of appropriate media in learning science subjects in elementary grades can positively impact their learning activities.